Kinetics and Mechanism of Nickel(II) Ion Biosorption by Immobilized Brown Algae - Wen Hong Fan; Zhi Zhen Xu; Qian Li (Adsorption Science & Technology)
The biosorption of Ni(II) ions by brown Laminaria japonica algae immobilized in sodium alginate and glutin beads was investigated. The kinetics of Ni(II) ion biosorption within the immobilized L. japonica beads were described well by the pseudo-second-order model. The equilibrium curves describing Ni(II) ion biosorption by the immobilized algal beads were fitted by the Langmuir and Freundlich isotherm models. The maximum biosorption capacity for Ni(II) ions in the immobilized algae beads was found to be 39.43 mg/g. Fourier-transform infrared spectrometric analysis of powdered L. japonica before and after biosorption of Ni(II) ions indicated that several functional groups in the algal cells (–OH, –NH 2 , –CH 2 , –CH 3 , –C=O, –N–H, –C–H, –C–O and –C=O) play an important role in the biosorption of Ni(II) ions by L. japonica .